Effect of dietary supplementation of different lutein sources on the productive performance of commercial layers categorized in three body weights - A. Sajjad, A.; Mahmud, A.; Akram , M.; Khalique, A.; Hussnain, F.; S. Haidary, A.; Khan, U.; Usman, M. (Scientific Journal of Zoology, 2013)
Lutein enrichment can be used for reducing chances of age related macular degeneration (AMD) in human being. The present study was conducted to evaluate the production performance of commercial layers categorized in three body weight categories supplemented with different lutein sources. For this purpose a total number of four thirty two 31 week old Hy-line (W-36) commercial layers were categorized in three body sizes (Heavy >1400g, Medium 1300-1399 g, Light <1300) and supplemented with different sources of Lutein (Control, Free, Esterified and Free + Esterified) replicated 6 times containing 6 birds each. The data were collected for production performance (egg production %, egg weight, egg mass, FCR per dozen, FCR per kg egg mass). The data were analyzed using analysis of variance (ANOVA) technique through Completely Randomized Design (CRD). Results of the present study showed non-significant (P>0.05) differences for production performance among different lutein sources and body weight categories except egg weight which was found to be highest in heavy birds. Thus Lutein can be supplemented in layer diet without any harm to its production performance.